EXPERIENCE WITH THE USE OF EVOLOCUMAB THERAPY IN PATIENTS WITH FAMILIAL HYPERCHOLESTEROLEMIA (IN KARELIA REPUBLIC) - V. A. Korneva; T. Yu. Kuznetsova; N. N. Natal’ya N. Vezikova (Евразийский Кардиологический Журнал, 2020)
Aim: to evaluate the efficacy and safety of the use of evolocumab in patients with familial hypercholesterolemia (FH).Materials and methods: Fifteen patients with a definite FH were treated with PCSK9 inhibitors, in 11 patients with a history of CAD. Eight patients (53.3%) received evolocumab (Repata) subcutaneously 140 mg once every 2 weeks, their average age was 51.4±2.3 years, 6 men. Lipid spectrum, ALT, AST, creatinine, glucose, Lp (a) were evaluated after 3, 6, 12 and 18 months, the ECG and the clinical picture were monitored. Evolocumab was prescribed in connection with the failure to achieve the target LDL. Before the start of therapy, 7 patients received statins, 5 statins with ezetemib, 1 patient did not receive lipid-lowering therapy due to intolerance. The target LDL levels were considered: for very high risk patients less than 1.4 mmol/L, high risk – less than 1.8 mmol/L. Statistical processing of the material was performed using STATISTICA10.0.Results: On the background of evolocumab therapy, the average level of LDL after 3 months of therapy decreased by 56.4% (from 3.9±0.3 to 1.71±0.2 mmol/L), the effect persisted after a year. All patients did not stop the therapy; there were no side effects, including local ones. Target LDL was achieved in 62.5% of patients, the average LDL level after 3 months of therapy decreased by 56.4% in patients from the initial, including the case of monotherapy with evolocumab. The Lp (a) level during therapy decreased by 30%.Conclusions: Evolocumab allows to increase the achievement of the target LDL level on 40% in FH patients; target LDL level was achieved in 62.5%. LDL decreased after 3 months by 56.4%, remaining stable with prolonged therapy. The decrease in Lp(a) reached 30%. Evolocumab therapy was characterized by high adherence and the absence of side effects.